PMO-077 Home enteral tube feeding (HETF): a case burden for the paediatric emergency department (PED)?. (28th May 2012) - Smith, J; Paxton, C; Leonard, P; Wilson, D
Abstract : Introduction: The contribution of HETF issues to PED workload is poorly understood. We aimed to evaluate PED attendance records of children receiving HETF (rates, presenting complaints and outcomes). We also aimed to assess possible trends between timing of attendances and hours of service provided by our Children's Community Nursing (CCN) team. Methods: We searched 114 606 attendances to PED from April 2008 to March 2011, reviewed all those involving cases on HETF, and correlated with our regional paediatric nutrition support team (NST) records. Day, time and month of attendance plus the presenting triage complaint and outcome were noted. Descriptive results are presented with day of week attendance analysed by the z-test. Results: There were 364 attendances of 183 patients with a mean (SD) annual point prevalence of HETF patients attending the PED of 23(3.1)%. Mean (SD) attendance rates were 121.3 (23.9) per year representing 61.0(5.2) patients. Presenting complaints included gastrostomy tube (GT) removal (29%), nasogastric tube (NGT) removal (27%), jejunal tube (JT) removal (5%) hardware fault (6%), tube blockage (12%), infection (9%), leakage (4%), malposition (5%) or other (3%). 324 (89%) patients were discharged home and 36 (11%) admitted, mostly for surgical reinsertion. More patients attended on Sundays than any other day of the week (p=0.045); December and January were the busiest months. Peak attendance time was 17:00–18:00; 43% attended out with CCN service hours (08:00–18:00). Most NGT and GT (64%) were reinserted in PED by medical, surgical or nursing staff. Imaging (fluoroscopy; chest x-ray) was required in 29 patients. Topical or enteral antibiotics were prescribed for 22 patients. No action or a simple flush was required in 24 and eight returned the following morning for placement. 20 repair kits for hardware problems were used. Conclusion: Over 20% of HETF attend PED annually with feeding tube-related problems; 43% attend out with CCN service hours. Significantly higher attendance rates on the day without CCN service cover highlights a flaw in this service design, given the simple problems that occur usually do not need PED expertise and resources. Competing interests: None declared. References: 1. Saavedra H, et al. Gastrostomy tube related complaints in the pediatric emergency department. Pediatr Emerg Care 2009;25 :728–32.